Pop Culture against Gravity. On Lightness in Advertising - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2024)
The author of the article (starting with the concept formulated by Italo Cavino in the American Lectures, which she reads critically) examines the manifestations and use of the category of lightness in persuasive messages. The analyzes of visual advertisements prove, among other things, that the creators of today's adverts saw various manifestations of lightness (both in terms of content and form) as a skillful way to express valuations and a convenient tool for creation. The study provides grounds for the recognition that not only literary works have the means to allow the viewer to “rise above the weight of reality” and enjoy “direct existence”. The author suggests that – taking into account the extremely wide spectrum of contextualization of lightness in texts representing popular culture, its persuasive meanings and the creative potential associated with it – what would be worth to consider in more detail, is the role of this category in the process of replacing the traditional “culture of needs” by the “culture of desires”.